2014
DOI: 10.1371/journal.pone.0108576
|View full text |Cite
|
Sign up to set email alerts
|

APP Is Cleaved by Bace1 in Pre-Synaptic Vesicles and Establishes a Pre-Synaptic Interactome, via Its Intracellular Domain, with Molecular Complexes that Regulate Pre-Synaptic Vesicles Functions

Abstract: Amyloid Precursor Protein (APP) is a type I membrane protein that undergoes extensive processing by secretases, including BACE1. Although mutations in APP and genes that regulate processing of APP, such as PSENs and BRI2/ITM2B, cause dementias, the normal function of APP in synaptic transmission, synaptic plasticity and memory formation is poorly understood. To grasp the biochemical mechanisms underlying the function of APP in the central nervous system, it is important to first define the sub-cellular localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 70 publications
4
56
2
Order By: Relevance
“…It is further hypothesized that homodimerized APP acts as a G-Protein coupled receptor which is activated by Aß and might be involved in neurotransmitter release following enhanced Ca 2+ influx. Especially the intracellular domains of APP and APLP2 seem to be associated with proteins of the synaptic vesicle release machinery regulating the molecular composition of synaptic vesicles at the presynaptic active zone (Del Prete et al, 2014; Fanutza et al, 2015; Laßek et al, 2015). At the postsynaptic compartment (Figure 2C) patterns of synaptic activity modulate APP family protein processing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is further hypothesized that homodimerized APP acts as a G-Protein coupled receptor which is activated by Aß and might be involved in neurotransmitter release following enhanced Ca 2+ influx. Especially the intracellular domains of APP and APLP2 seem to be associated with proteins of the synaptic vesicle release machinery regulating the molecular composition of synaptic vesicles at the presynaptic active zone (Del Prete et al, 2014; Fanutza et al, 2015; Laßek et al, 2015). At the postsynaptic compartment (Figure 2C) patterns of synaptic activity modulate APP family protein processing.…”
Section: Resultsmentioning
confidence: 99%
“…APP and APLP2 show a variety of possible interactions with the synaptic vesicle release machinery: Biochemical approaches showed that APP is associated with synaptic vesicle proteins (Del Prete et al, 2014; Laßek et al, 2014) and that it can be cleaved within vesicles by BACE-1 (Del Prete et al, 2014). Especially the intracellular regions of APP, APLP2, and CTF-ß have been shown to interact with presynaptic vesicle proteins like Rab, AP-2 subunits, the Ca 2+ sensors synaptotagmins, clathrin, and complexin (Del Prete et al, 2014; Fanutza et al, 2015). Results from APP-KO animals point toward a role of APP in controlling synaptic vesicle protein content in the presynaptic active zone as synaptophysin, synaptotagmin-1, and SV2A protein levels are reduced in APP KO mice.…”
Section: Presynaptic Function Of App Family Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…This short sequence lacks enzymatic activity and may function as a docking domain for cytosolic as well as membrane-bound proteins (46,(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72). To explore the potential role of the ACR, we used a proteomic approach (28,48 ), and St-ACR with phosphorylation on both Thr 668 and Tyr 682 (St-ACR Thr(P)Tyr(P) ), were immobilized on StrepTactin resin. The numbering of phosphorylated residues is based on the APP isoform of 695 amino acids.…”
Section: App Interacts Via Its Acr With Proteins Thatmentioning
confidence: 99%
“…Using an unbiased proteomic approach, we have characterized the ACR brain interactome (28,48). Here, we show that the ACR interacts with several proteins that regulate the UPS.…”
mentioning
confidence: 99%